Awareness and Implementation of Automated Accounting System for a State University in Pangasinan, Philippines - Jeanilyn L. Villanueva (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
The study proposed a cost-effective automated accounting system for a State University in Pangasinan, applicable to other higher education institutions. Using a mixed-method research design, the study collected both qualitative and quantitative data through a Focus Group Discussion with key university officials from the accounting department and a survey of 100 accounting personnel across nine campuses, an open university system, and a school of advanced studies during the fourth quarter of 2023. Additionally, the study revisited various legal issuances and related documents to perform a comparative cost-effectiveness analysis between the existing manual system and the proposed automated accounting system. Findings revealed that, although the accounting personnel are generally aware of the current processes, there is a moderately serious problem with the existing system, particularly regarding its features. The cost analysis showed potential savings of P1,052,950.56 over three years with automation. The study recommends implementing the proposed automated accounting system to improve efficiency and cost-effectiveness, which could serve as a model for other higher education institutions.